Maharah al-Qiroah Fi al-Madrasah al-Tsanawiyah al-Hukumiyah Air Bangis Pasaman al-Gharbiyah (Dirasah Tahliliyah An Tadrisiha wa Shuubatiha) - Rahadian Kurniawan (Institut Agama Islam Negeri Curup, 2018)
This study deals with the teaching of reading skills and its difficulty in the high school Air Bangis in West Pasaman. The research methodology in this study is qualitative field research in analytical type. The problems in the process of teaching reading skills in the government high school Air Bangis in West Pasaman, the teacher lack of interest in the use of teaching aids to achieve the desired goals in the teaching of reading, and do not have exercises to develop the skill of reading for students, but exercises in the textbook. And the lack of interest of the teacher to defend students in the teaching of the Arabic language. In the process of teaching reading skills, the difficulties in terms of pupils, including: teams of intelligence, and lack of tendencies of some students in teaching, and the background of their upbringing. And their difficulties in terms of teachers of the Arabic language, including lack of interest in the use of the various educational method, lack of resources on the teaching of modern Arabic. These comprehensive problems need treatment, it is the teacher's interest in the teaching curriculum, and the teacher to design teaching in the teaching of reading skills in this school.